Overview of Personal Hygiene and Environmental Sanitation in Shared Living with Scabies: Literature Review - Zuhrohtan Anglian Nisaa'; Kusuma S. Lestari (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Scabies is a disease caused by Sracoptes scabiei which is in the form of itching all over the body. This disease tends to occur in places with a fairly low Human Development Index and is one of the diseases that is still ignored in developing countries such as Indonesia. Scabies disease in Indonesia has a fairly high prevalence. This disease is closely related to personal hygiene and environmental sanitation in a person's residence. This disease is easier to spread when an individual's space is small and lives in the same place Objective: This study aims to provide information related to sanitary and personal hygine features with scabies disease in shared residences to minimize the prevalence of scabies disease Method: This study uses the method of reviewing literature on journal articles published within the last five years related to the topic of discussion. Data retrieval techniques using Google Scholar, Pubmed, and Scopus. Then, in the corresponding article eliminated is carried out. Result: Four different articles on shared residences namely orphanages, detention centers, foundations, and Islamic boarding schools have a poor sanitation and personal hygiene at high risk of scabies. These four residences have the same characteristics, namely co-living with limited personal space. The manager and those who live in a shared residence must have awareness in maintaining environmental sanitation and know the importance of personal hygiene. Conclusion: This study recommends to stakeholders, health care providers, and other parties to follow up on scabies prevention efforts. Moreover, for places that providing shared living needs to watch over the sanitation and personal hygiene from its environment and people who lived in the neighborhood.